Analisis Sentimen Stakeholder Atas Layanan Haidjpb Pada Media Sosial Twitter Dengan Menggunakan Metode Support Vector Machine Dan Naïve Bayes - muhammad luthfiy kurniawan harsono; Yuris Alkhalifi; Nurajijah; Windu Gata (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2022)
Creation of a special account on social media Instagram and Twitter that aims to accommodate the delivery of questions, input, criticism and suggestions from stakeholders around the ongoing business processes and the use of applications in the framework of budget planning, commitment making, disbursement of the state budget, accounting receipts and financial reporting based on the fact that social media cannot be separated from community activities because the presence of digital devices (smartphones) and affordable internet access makes various groups of people able to obtain information quickly and easily. Organizations have an interest in getting benchmarks for services that have been provided in order to improve the quality of services going forward based on tweets data obtained from Twitter social media. This study discusses the process of collecting and processing tweet data on the @haiDJPb account in order to perform stakeholder sentiment analysis of haiDJPb services on twitter social media using Support Vector Machine and Naïve Bayes algorithms and the accuracy of the Support Vector Machine algorithm is 74.55 % and 77.18% for the Naïve Bayes algorithm.